MOORE, KENNETH RYCE (ED.). BRILL’S COMPANION TO THE RECEPTION OF ALEXANDER THE GREAT. LEIDEN/BOSTON: BRILL, 2018. 855 p. ISBN: 978-90-04-28507-1. - Thiago do Amaral Biazotto (Heródoto, 2020)
Resenha - BRILL’S COMPANION TO THE RECEPTION OF ALEXANDER THE GREAT.